Factors Associated With Anxiety Symptoms in Older Adults Attending an Outpatient Geriatric Service: A Cross‐Sectional Study - Gianella Grajeda‐León; Victoria Azurin‐Gonzales; Zulema Mamani‐Condori; Alvaro M. Ñaña‐Cordova; Marina A. Bustamante‐Ordoñez; Fiorella Neyra‐Cordova; José F. Parodi; Fernando M. Runzer Colmenares (Aging Medicine, 2025)
ABSTRACT Objective To identify the factors contributing to anxiety among adults aged 65 and older receiving care at the Geriatric Service of the Naval Medical Center. Methods An analytical study was conducted through secondary analysis of a database from a study carried out between 2010 and 2015 at the Naval Medical Center of Peru (CEMENA). The data from 1686 participants were analyzed, with anxiety as the dependent variable, measured using the Hamilton Anxiety Rating Scale with a cutoff point of 14. The analysis was performed using STATA software. Bivariate analysis was conducted using the chi‐squared and Student t‐tests, while Poisson regression was employed for multivariate analysis to determine the frequencies and associations between anxiety and the various variables. Results In the multivariate analysis, anxiety was found to be significantly associated with gait speed (PR 1.11; 95% CI 1.03–1.20), depressive symptoms (PR 1.97; 95% CI 1.81–2.16), polypharmacy (PR 1.14; 95% CI 1.04–1.06), and education level (PR 0.83; 95% CI 0.76–0.90). Additionally, marital status was found to be associated with the likelihood of anxiety: being married (PR 0.64; 95% CI 0.53–0.77), widowed (PR 0.54; 95% CI 0.44–0.66), or divorced (PR 0.63; 95% CI 0.49–0.83) were all linked to a lower probability of anxiety compared to being single. Conclusion Factors such as depressive symptoms, polypharmacy, slow gait speed, education level, and marital status were found to be associated with anxiety in older adults.